Demorest Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1881)
Demorest's Family Magazine. 1881. -- Miss Spinner's Diary -- Though the Harbor Bar be Moaning -- Russell's Drawing -- The Fragment of a Photograph -- The Herdsman -- Fra Angelico di Fiesole -- Nerves -- Spring-Time -- Teach me to Live -- The Tragic Story of a Diamond Necklace -- Kith and Kin -- My Housekeeping Class -- Decorative Art and the Associated Artists -- Stories from the Classics -- A Murdered Woman -- Prunes and Prisms -- European Letter -- Current Topics -- Kitchen -- Mirror of Fashions -- Visiting Toilets --
Mme Demorest's Mirror of Fashions
New York Illustrated News
Pages 139-142 torn. Digitized from original print, Valdosta State University Archives and Special Collections, November 3, 2017.
Keywords: Demorest's Family Magazine; Magazine; Illustrated Periodicals; Periodicals; Travel; Dressmaking; Homemaking; Needlework; Women; Social History; Children; Women's History; Fashion; United States; 1800s; 19th Century